2022
DOI: 10.4018/ijhcitp.293231
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Career Success and Career Advancement of Women

Abstract: Ever since there have been a lot of challenges that a woman has to go through to make her career a success. The study focuses on the challenges that women face as a resultant of organizational and family barriers. The current study aims to test whether mentoring, Perceived Organizational Support (POS), and Family Responsibilities (FR) have an impact on Perceived Career Success (PCS) and career advancement of women working in the Indian IT industry. 307 respondents have been analyzed and the reliability and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…For Ingarianti et al (2022), the term career denotes "a path an individual goes through related to their life-long work activities". It is defined by Chauhan, Mishra and Bhakri (2022) as an individual's work-related and other relevant experiences, both inside and outside of organisations, which form a unique pattern over the individual's life span. Beginning in the 1980s, research on PCS was conducted and the construct was then defined by London and Stumpf (1982) as a good psychological sensation or related work accomplishment that one individual has steadily amassed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For Ingarianti et al (2022), the term career denotes "a path an individual goes through related to their life-long work activities". It is defined by Chauhan, Mishra and Bhakri (2022) as an individual's work-related and other relevant experiences, both inside and outside of organisations, which form a unique pattern over the individual's life span. Beginning in the 1980s, research on PCS was conducted and the construct was then defined by London and Stumpf (1982) as a good psychological sensation or related work accomplishment that one individual has steadily amassed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because men and women have different paths, needs and challenges for their career advancement, especially female employees who have difficulty getting promotions to the highest positions in the organizations where they work. Research conducted by Chauhan et al (2022) identified two factors that need to be considered in making employee career advancement successful, namely Perceived Organizational Support (POS), and Family Responsibilities (FR). Apart from that, other factors such as family-friendly employment practices, transparent and proactive gender policies, mentoring, and Self-Development Planning are also important factors for the career advancement of female employees.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals naturally want to succeed in their careers; the type of success they experience relies on their expectations (Chauhan et al, 2022). From the perspectives of both employees and employers, career success is crucial (Spurk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%